Accessibility Evaluation of Design Patterns on Moodle Mobile - Casadei, Vitor; Zaina, Luciana; Pinheiro, Eduardo; Granollers, Toni (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2016: Anais do XXVII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2016.688, 2016)
An universal accessibility evaluation of the Moodle Mobile app from a study with 21 participants without disabilities is presented by assessing the emotional response to seven interaction design patterns and video analysis. Results show accessibility barriers identified during the execution of activities and implications of these barriers in the learning process.